Home remedies in different pediatric dermatoses: An observational study. Issue 6 (3rd September 2020) - Gupta, Mrinal; Bhargava, Shashank
Abstract: Traditional medicinal systems are widely practiced in the Indian subcontinent for a wide variety of diseases. We aimed to identify the various home remedies used by people to treat numerous pediatric dermatoses. It was an observational study carried out over 18 months in which 150 children attending our clinics were recruited. A detailed history regarding the various indigenous preparations used was taken from caregivers and noted in a proforma. A total of 150 children (M:F‐89:61) aged between 4 months to 18 years were included. Atopic dermatitis and eczema (n = 28) were the most common dermatoses whereas the most common home remedies used for these either solo or in combination were coconut oil (13), olive oil (11), mustard oil (7), aloevera gel (6), ghee (6), curd (4), and honey (2). Acne was the second most common dermatoses (n = 22), products used for acne were Fuller's earth, aloevera gel, turmeric, gram flour, mustard oil, lime and sandalwood paste. Other dermatoses treated by indigenous products included impetigo and other bacterial infections, seborrheic dermatitis, dermatophytoses, verruca, molluscum, hypopigmentary disorders, etc. In Indian setup, home remedies are commonly used by the caregivers before visiting a dermatologist to treat various pediatric dermatoses.